2022
DOI: 10.1016/j.jtcvs.2020.09.138
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac surgery outcomes in patients with coronavirus disease 2019 (COVID-19): A case-series report

Abstract: Objective The impact of COVID-19 on the post-operative course of patients after cardiac surgery is unknown. We experienced a major Sars-CoV-2 outbreak in our cardiac surgery unit, with several patients that tested positive early after surgery. Here we describe the characteristics, the post-operative course and laboratory findings of these patients, along with the fate of the health-care workers. We also discuss how we reorganize and reallocate hospital resources in order to resume the surgical act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 23 publications
2
29
1
2
Order By: Relevance
“…8 It is well established that the extracorporeal circulation generates a systemic inflammatory response syndrome and that severe acute respiratory syndrome (SARS) from COVID-19 may lead to "cytokine storm" resulting in shock and death, as reported by a cardiovascular division in Italy. 9,10 It has been reported that patients who underwent cardiac surgery during 2020 have been infected with COVID-19, and that patients with CVD are more likely to have a severe presentation of SARS from COVID-19. 11 Another major concern is that patients with CVD disease are afraid to call emergency assistance or go to emergency rooms for fear of contracting COVID-19 or burdening an already-overwhelmed health-care system.…”
Section: Discussionmentioning
confidence: 99%
“…8 It is well established that the extracorporeal circulation generates a systemic inflammatory response syndrome and that severe acute respiratory syndrome (SARS) from COVID-19 may lead to "cytokine storm" resulting in shock and death, as reported by a cardiovascular division in Italy. 9,10 It has been reported that patients who underwent cardiac surgery during 2020 have been infected with COVID-19, and that patients with CVD are more likely to have a severe presentation of SARS from COVID-19. 11 Another major concern is that patients with CVD disease are afraid to call emergency assistance or go to emergency rooms for fear of contracting COVID-19 or burdening an already-overwhelmed health-care system.…”
Section: Discussionmentioning
confidence: 99%
“…Guo et al 23 collected and analyzed swabs taken in different hospital locations and reported a greater risk of SARS‐COV‐2 in ICU than in general wards. In Maria Eleanora Hospital, Italy, 20 patients were found positive for SARS‐COV‐2 post‐surgery among the 55 inpatients, of these 20 patients, 18 underwent cardiac surgery while 2 of them underwent trans catheter aortic valve replacement 26 …”
Section: Methodsmentioning
confidence: 99%
“…A small study in cardiac surgery patients had a mortality of 15% among patients who had cardiac surgery and acquired COVID-19. 1 Mortality in patients undergoing lung cancer surgery appears even higher at 27%. 2 There is little available data on esophagectomy performed during the COVID 19 pandemic.…”
mentioning
confidence: 99%